Development of green blended binder consisting of high-volume slag and fly ash with nano CSH seed accelerator - Imihami Mudiyanselage, Kumuditha Sathyajith Senadheera (Curtin University, 2024)
This thesis presents the effectiveness of using calcium silicate hydrate (C-S-H) seed accelerator as an admixture to compensate early age strength development in cement binder containing high volume fly ash and slag towards development of sustainable binder. Three types of sustainable binders are considered with addition of 2.5%,5% and 7.5% C-S-H seed accelerator along with slag, fly ash and slag and fly ash combination with 70%,80% and 90% replacement in OPC.